Global business citizenship a transformative framework for ethics and sustainable capitalism - Wood, Donna J.; Logsdon, Jeanne M.; Lewellyn, Patsy G.; Davenport, Kim (M.E. Sharpe, Inc., 2006)
Provides a coherent approach to global business responsibility and ethics based on the research, theory, and practice. Incorporating numerous real world examples, this book focuses on the strategic alignment and change management process for implementing business citizenship principles and practices